Pendekatan Penginjilan Kontekstual Terhadap Budaya Pekan Gawai Suku Dayak - Akanpeni, Trisilpa; Saputra, Roland Holy; Ina, Ernesta Tamo; Tansi, Filmon Gusti (Jurnal Kala Nea, 2021)
This study analyzes the culture of Gawai Week to assist in finding cultural meaning and assisting in the evangelistic approach to gawai week culture. Through this gadget week, the Dayak tribe can gather to hold various attractions as well as socialize in it. This custom is carried out once a year involving the entire Dayak community. The custom of this gawai week still believes in the abundance of blessings received from the ancestors. Through this habit, it is used as a contextualized medium for evangelism. By taking a persuasive approach in order to be able to change a good and correct perspective on the blessings received through the gadget week. It is this good perspective that can change perspectives and can also incorporate the Bible into the culture of gadget week to understand where the words are received in gadget week.